La classe inversée pour l’enseignement de la grammaire et de l’oral dans le contexte algérien - Lamia Boukerchi; Naima Ould Benali (Multilinguales)
In the continuity of a subsequent research work relating to hybrid teaching in FLE license, the present article attempts to remedy the shortcomings encountered, case of the University of Bejaia, Algeria. The latter is based on the principle of the flipped classroom. Its main purpose is to focus on course models and activities to be worked on in continuity (online and face-to-face) and takes a great interest in the knowledge taught and its acquisition on the methodological and linguistic level within the framework of a formative evaluation.